PENGARUH REWARD TERHADAP KEPUASAN KERJA KARYAWAN DI PDAM TIRTA LONTAR KABUPATEN KUPANG - Ephivania Eunike Foenay; Rolland E Fanggidae; Wehelmina Mariana Ndoen (Journal of Management Small and Medium Enterprises (SMEs), 2020)
This study aims to determine the influence of reward on job satisfaction in PDAM Tirta Lontar,Kupang Regency. The method used in this study is a survey method with a quantitative approach.The sample in this study was taken using simple random sampling technique with Slovin method bytaking 67 respondents from the entire population. Primary data obtained by questionnaire filleddirectly by the respondent. The results of this study indicate that the reward is positive and significantwith a coefficient of 1.095 and a significance level of 0.000 < 0.05. Keywords: Job Satisfaction, Reward